Add-on Lamotrigine Treatment for Subsyndromal Depression after Manic or Mixed States in Bipolar Disorder Improved the Quality of Life. (23rd September 2012) - Muneoka, Katsumasa; Kon, Katsushi; Kawabe, Masaharu; Ui, Rui; Miura, Taichi; Iimura, Touta; Kimura, Shou
Abstract : Two cases of patients experienced subsyndromal depression after manic or mixed hypomanic and depressive episodes due to bipolar I (case 1) and II (case 2) disorders prior to the use of lamotrigine. Case 1 showed episodes of mood switching induced by antidepressants and seasonal mood instability. Case 2 showed hippocampal atrophy and a persistent dull headache that preceded the use of lamotrigine. Both were successfully treated with add-on lamotrigine therapy, and the dull headache was effectively treated with olanzapine. Both patients improved in social activity and work performance after these add-on treatments. Thus, add-on treatment with lamotrigine alone or in combination with olanzapine was an effective strategy to improve the quality of life in bipolar depression. Subsyndromal depression that present after the disappearance of the manic or mixed state was suggested to be practical indication for the use of lamotrigine.